The First 10 Years: Reflecting on Opportunities and Challenges of the Tobacco Products Scientific Advisory Committee of the United States Food and Drug Administration. Issue 3 (19th January 2021) - Fagan, Pebbles; Eissenberg, Thomas; Jones, Dina M.; Cohen, Joanna E.; Nez Henderson, Patricia; Clanton, Mark S.
Abstract: Introduction: Tobacco control policies have helped to reduce the health, social, and economic burden of commercial tobacco use worldwide. Little is known about the long-term impact of regulatory policies and functioning bodies that make recommendations to inform policies. The Tobacco Products Scientific Advisory Committee (TPSAC) of the U.S. Food and Drug Administration (FDA) was formed in 2009 to evaluate the safety, health, and dependence of tobacco products and provide related advice and recommendations to the FDA and the Secretary of Health and Human Services. This article describes the first 10 years of the TPSAC activities and reflects on the impact of their service on regulatory actions. Methods: We reviewed public documents from the 2010–2019 TPSAC meetings to examine the purposes, TPSAC decisions, public health participation in meetings, and concordance of the TPSAC recommendations with regulatory actions. Meeting agendas, transcripts, public testimony, and presentations were reviewed to obtain this information. Results: Since 2010, the TPSAC held 25 public meetings with 178 speakers who provided oral public testimony. Sixty-four percent of meetings were held from 2010 to 2012, when three congressionally mandated reports were due on the topics of menthol cigarettes, harmful and potentially harmful constituents in tobacco products, and dissolvable tobacco products. Forty-four percent of meetings focused on menthol cigarettes, 32% on modified risk tobacco products, 16% on harmful and potentially harmful constituents, 12% on dissolvable tobacco, and 4% on tobacco addiction/dependence. FDA regulatory actions were largely nonconcordant with voting decisions by TPSAC. Conclusions: The TPSAC has evaluated an enormous amount of science during the first 10 years, but their influence on regulatory policies has been limited. The TPSAC roles and functioning should be reevaluated to determine how TPSAC can better fulfill its mandate to inform the FDA's regulatory decision making, which could ultimately reduce the burden of tobacco use in the United States.